Website profile development for digitalization of grass jelly based MSMEs - Yohanes Setiawan; Riza Akhsani Setyo Prayoga; Fauzan Nusyura; Muhammad Anjas Ardiansyah; Machfud Ichsan Khoirudin; Muhammad Rashid Syaputra (University of Merdeka Malang, 2023)
Technology has developed vastly through digitalization for every business sector, e.g., Micro, Small, and Medium Enterprises (MSME), in developing website profiling as sources of information and advertisement. Kampung Cincau is a village located in Surabaya, East Java, Indonesia which produces grass jelly (cincau) and has been known through mass media coverage. However, they do not have specific and updated information access personally to be accessible to the public. The main objective of this community service is developing a website profile as a source of promotion in Kampung Cincau. There are three steps to developing a website in Kampung Cincau, i.e., preparation, implementation, and ending by monitoring and evaluation. Communicating with the people in Kampung Cincau to dive deeper into their needs has been done as preparation. Afterward, implementation covers finishing the website and writing the website’s manual book. Lastly, monitoring and evaluation focus on conducting admin training for the website to the people and monitoring them as if they have difficulties maintaining the website. These three steps have been finished as sequences of the community service program in Kampung Cincau. Based on the results of a survey on the implementation of community service through Google Forms, the people of Kampung Cincau is assisted through the output of a website profile that has been built and requires assistance in the optimization of utilizing the website.